Reliability and concurrent validity of the iHandy level mobile application to measure thoracolumbar range of motion in low back pain patients - Ijaz, Nimra; Riaz, Saima; Raza, Tahreem; Ali, Sidra (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Introduction. The use of smartphone technology and software (apps), in addition to an inclinometer and goniometer, has ex-panded the clinician’s assessment possibilities. However, the legitimacy and trustworthiness of these cell phones and applications are still questioned. This study aimed to determine the reliability and concurrent validity of the iHandy level mobile application to measure the thoracolumbar range of motion in people with low back pain.Methods. This descriptive study included 40 participants, of which 20 were symptomatic, and 20 were asymptomatic for non-speciﬁc chronic pain in the lower back. Measurements were taken for extension, ﬂexion, and left and right-side bending range of motion (ROM). Two investigators were involved. One measured ROM values with a Samsung iHandy level and inclinometer, and the second investigator registered the data. Two values were taken and the mean was used for further analysis. Measure-ments were taken at baseline and one-week follow-up.Results. In asymptomatic participants, the mobile application had ICC values of 0.81, 0.70, 0.79, and 0.85, while in symptomatic, regarding intra-rater reliability, these were 0.80, 0.78, 0.81Regarding the concurrent validity of mobile apps in asymptomatic patients, ICC values were 0.94, 0.93, 0.84, and 0.89, while in symptomatic patients, the ICC values were found to be 0.92, 0.89, 0.83, and 0.85 for ﬂexion, extension, RLF, and LLF, respectively. These showed an excellent correlation between the inclinometer and mobile app regarding intra-rater reliability and concurrent validity.Conclusions. iHandy level smartphone applications might be considered reliable and valid for assessing thoracolumbar motion ranges in individuals with chronic pain in the lower back.
Keywords: low back pain; range of motion; lumbar spine; inclinometer; mobile application